Simultaneous phase measurement interferometry for laser interaction in air - Yahaya, Asiah (2006)
The problem encountered when evaluating phase profile of laser interacted images with direct phase mapping method, using only one interferogram, was in the form of phase ambiguity. This was due the existence of extra fringes in the interacted region of the interferogram. The very sensitive Phase Measurement Interferometry (PMI) also suffers from environmental factors such as vibrations and air turbulence. The new system developed to reduce phase ambiguity was a three outputs interferometer, which was designed to capture three interferograms simultaneously. The fast photography incorporated in the system managed to eliminate the problems of vibrations and air turbulence. The three interferogarms were initially arranged to have a phase difference of 90° with one another; a requirement for quadrature imaging. Since the interferograms were captured simultaneously, they would carry different phase information of the event. The acoustic wave generated by laser interaction caused the fringes to deviate accordingly to the change in its phase. From their three intensities, appropriate phase shifting algorithms were selected to produce a single final phase change profile of the interaction event. The result obtained revealed a significant contribution to the reduction in phase ambiguity. The changes in phase were associated with the changes in refractive index, density and pressure. The values of pressure change were compared to those obtained from the conventional fringe analysis. Measurements made at time delay of 3.6 µs indicated a 26 % difference. As the delay increased, this difference seemed to decrease and at around 5.0 µs both techniques seemed to produce agreeable results. The nonlinear profiles of the maximum pressure change with time using the two techniques were presented. Despite the high complexity of the experimental setup, the system managed to fulfill the objectives for its development